42. SURVEY ON MEDICATION ADHERENCE OF HEART FAILURE PATIENTS AT UNIVERSITY MEDICAL CENTER HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the current state of medication adherence in patients with heart failure and identify related factors.Research objects and methods: Cross-sectional descriptive study conducted at the Cardiology Clinic and Heart Failure Clinic, Ho Chi Minh city University of Medicine and Pharmacy Hospital during the period from September 2023 to May 2024. Patients or legal representatives fill out the pre-designed survey questionnaire themselvesResults: The study included 340 patients. The rate of medication adherence among heart failure patients was 94.7%, while the non-adherence rate was 5.3%. Among them, high medication adherence was 69.4%, moderate adherence was 25.3%, and low adherence was 5.3%. Factors related to medication adherence included age, educational level, income, causes of heart failure, duration of heart failure and medication habits.Conclusion: The rate of medication adherence in heart failure patients is relatively high. Patients with poor economic conditions, and long-term heart failure are associated with poor adherence. This group of patients should receive more attention from healthcare professionals.
Keywords: Heart failure, adherence, medication.